In Vitro Screening and Transfection Concentration Optimization of Cynomolgus Monkey IκBα-siRNA - Zhaoxing Ou; Rui Zeng; Yifan Lin; Si Zhang; Mohammad Alzogool; Peng Zeng; Yuqing Lan (Journal of Ophthalmology)
Purpose. To seek for a small interfering RNA (siRNA) sequence targeting a cynomolgus monkey inhibitor of nuclear factor kappa B α (IκBα) that can specifically and effectively suppress IκBα gene expression of cynomolgus monkey ciliary muscle (CM) cells and trabecular meshwork (TM) cells in vitro and screen for optimal siRNA transfection concentration. Methods. Three IκBα-specific double-stranded siRNAs were designed and synthesized. They were transfected into primarily cultured cynomolgus monkey CM cells and TM cells. The mRNA and protein levels of IκBα were examined by using real-time quantitative polymerase chain reaction (real-time PCR) and western blot to screen a pair of candidate valid sequences with the highest inhibitory rate. Both cells were transfected with Cy5-labeled nonspecific control-siRNA (NC-siRNA) of four different concentrations (10, 20, 50, and 100 nmol/L(nM)), and flow cytometry was used to assess transfection efficiency. Then, cells were transfected with the candidate valid IκBα -siRNA of the same four concentrations, and the cytotoxicity was detected by using Cell Counting Kit-8 (CCK8), and the inhibitory efficiency of IκBα was identified via real-time PCR to find out optimal siRNA transfection concentration. Results. The suppression effect of the siRNA targeting the GCACTTAGCCTCTATCCAT of IκBα gene was most obvious by in vitro screening. The inhibitory rate of IκBα was 82% for CM cells and 82% for TM cells on the mRNA level and 98% for CM cells and 93% for TM cells on the protein level, respectively. The results of flow cytometry showed that the transfection efficiency was the highest at 100 nM, which was 89.0% for CM cells and 48.2% for TM cells, respectively. The results of CCK8 showed that there was no statistically significant difference in cell viability after transfection of different concentrations of IκBα-siRNA. The results of real-time PCR indicated that there was no statistical difference in the inhibitory efficiency of IκBα after transfection of different concentrations of IκBα-siRNA. Conclusion. It proves that the siRNA targeting the GCACTTAGCCTCTATCCAT of IκBα gene is the valid sequence to suppress cynomolgus monkey IκBα expression of CM cells and TM cells by RNAi. 10 nM is the optimal transfection concentration.